Preparation and application of anode-free sodium metal batteries and their modified current collectors
By using modified current collectors, modified materials and conductive agents containing modified layers in negative electrode sodium metal batteries, the problem of low growth and circulation efficiency of sodium dendrites is solved, and high-performance battery assembly and stability is achieved. Adaptable application requirements for high surface load positive electrode.
Patent Information
- Application Number
- CN202411455906.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-18
AI Technical Summary
The negative electrode current collector of the negative electrode without anode sodium metal battery has difficult challenges in the growth of sodium dendrite, low circulation efficiency and poor stability, especially in the assembly of high surface load positive electrodes, it is difficult to form a battery with high circulation stability. .
A modified current collector containing a modified layer is used. The modified layer is composed of a binder, a conductive agent and a modified material. The modified materials include Y2O3, Gd2O3, yttrium carbonate, etc. The weight ratio of the modified layer is 20~80: 10~60:10~20, with a thickness of 20~100μm, which can induce uniform deposition of sodium metal and inhibit sodium expansion and dendrites growth.
It significantly improves the electrochemical performance of the negative electrode-free sodium battery, improves the reversibility and cycle efficiency of sodium deposition, meets the high specification requirements of high surface load positive electrodes, and realizes high-performance battery assembly.
Smart Images

Figure CN119029214B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of negative electrode-free sodium metal batteries, and in particular to a negative electrode current collector of a negative electrode-free sodium metal battery. Background Art
[0002] As the application of lithium-ion battery technology in consumer electronics, electric vehicles, energy storage and other markets gradually expands, the problem of insufficient lithium resources has also begun to emerge. Sodium-based batteries have gradually attracted attention because the earth has a sufficiently high abundance of sodium elements, and they have an important strategic position in application fields with high cost requirements such as energy storage. The large-scale application of sodium-ion batteries is limited by problems such as low specific capacity of sodium-ion batteries.
[0003] The anode-free battery does not have any sodium ion embedding material on the anode side, only the anode current collector, and can work as a sodium metal battery after the initial charging process, thereby providing a higher operating voltage and significantly improving the volume energy density and mass energy density due to the reduction in battery volume and weight. However, compared with electrodes with anode active materials, the anode current collector of the anode-free sodium metal battery needs to overcome more prominent problems such as sodium dendrite growth, low cycle efficiency and poor stability.
[0004] The prior art also discloses some improvement means. For example, the Chinese patent document with publication number CN117747847A discloses a composite current collector with a sodium-philic interface, its preparation and application in a negative electrode-free sodium battery, which relates to a composite current collector with a sodium-philic interface, including a current collector and a sodium-philic interface layer composited on its surface, wherein the sodium-philic interface layer includes a metal M matrix and a metal M-metal N alloy phase uniformly dispersed therein; the metal M includes at least one of Cu, Fe, Ni and Ti; the metal N includes at least one of Sb, Bi, In, Ag, Pb and Sn; in the sodium-philic interface layer, the content of the metal N is 8-25wt%. For another example, the Chinese patent document with publication number CN117727948A discloses a negative electrode current collector and its preparation method, a sodium secondary battery and an electrical device, wherein the negative electrode current collector includes a substrate; a functional layer, wherein the functional layer is arranged on at least one side of the substrate, and the functional layer includes a multifunctional additive, wherein the multifunctional additive includes Na x MN y ·zH2O, wherein M includes atoms that can form an alloy with Na, N includes at least one of O atoms, S atoms, and Se atoms, and 0 <x≤5,0<y≤5,0≤z≤5。
[0005] In summary, although the existing technology can improve the performance of the current collector in the negative electrode-free sodium battery to a certain extent, there is still room for improvement. In particular, it is difficult to further adapt to the use requirements of high surface loading positive electrodes, and it is difficult to assemble with high surface loading positive electrodes to form a negative electrode-free battery with high cycle stability. Summary of the invention
[0006] In view of the problems faced by the negative electrode collectors of existing negative electrode-free batteries, the first purpose of the present invention is to provide a modified current collector for negative electrode-free sodium batteries (also referred to as a negative electrode current collector in the present invention), aiming to provide a modified current collector that is adapted to the application requirements of negative electrode-free batteries and has excellent performance such as capacity and cycle stability.
[0007] The second object of the present invention is to provide a method for preparing the modified current collector and its application in a negative electrode-free sodium metal battery.
[0008] The present invention also provides a negative electrode-free sodium metal battery comprising the modified current collector.
[0009] Compared with the negative electrode of conventional negative electrode active materials, the negative electrode current collector of the negative electrode-free sodium battery has greater difficulty in controlling sodium dendrites, sodium uniform induction, and sodium expansion. It is more difficult to assemble with the high-surface-loaded positive electrode to obtain a high-performance negative electrode-free battery. In view of the problems faced by the negative electrode current collector of the negative electrode-free sodium battery, the present invention has been studied in depth and provides the following improvement scheme:
[0010] A modified current collector for a negative electrode-free sodium metal battery, comprising a planar current collector and a single-layer modified layer composited on the surface thereof; the modified layer is composed of a binder, a conductive agent and a modified material; the modified material comprises at least one of Y2O3, Gd2O3, yttrium carbonate, lead carbonate, tungsten carbonate, iridium carbonate, hafnium carbonate, molybdenum carbonate, gadolinium carbonate, yttrium titanate, iridium titanate, hafnium titanate, molybdenum titanate and gadolinium titanate;
[0011] Wherein, in the modified layer, the weight ratio of the modified material, the conductive agent, and the binder is 20~80:10~60:10~20;
[0012] The thickness of the modified layer is 20~100μm.
[0013] The innovative research of the present invention shows that the modified current collector containing the modified material can adapt to the application requirements of negative electrode-free sodium batteries, can induce uniform deposition of sodium metal, and can inhibit sodium expansion. Not only that, it can also effectively inhibit sodium dendrites. Applying it to negative electrode-free sodium batteries can significantly improve its electrochemical performance.
[0014] The particle size of the modified material described in the present invention can be 10-1000 nm.
[0015] In the present invention, the modified material comprises component A and component B;
[0016] Wherein, the component A includes at least one of Y2O3 and Gd2O3;
[0017] The component B includes at least one of yttrium carbonate, lead carbonate, tungsten carbonate, iridium carbonate, hafnium carbonate, molybdenum carbonate, yttrium titanate, iridium titanate, hafnium titanate, molybdenum titanate, gadolinium carbonate and gadolinium titanate.
[0018] Preferably, the weight ratio of component A to component B is 10-30:70-90. Studies have shown that the combination of the special oxidation type component A and the special salt type component B can unexpectedly achieve synergy, further enhance the adaptability of the modified material to the high surface load positive electrode, and further enhance the electrochemical performance of the high surface load positive electrode-no negative electrode battery.
[0019] The present invention has shown that the use of a combination of component A and component B can further achieve synergy, can further adapt to the application requirements of no negative electrode metal, and can obtain better electrochemical performance.
[0020] In the present invention, the planar current collector is a conductive metal foil, preferably copper foil, aluminum foil, carbon-coated aluminum foil, carbon-coated copper foil, carbon cloth or iron foil.
[0021] In the present invention, the binder includes at least one of PVDF, CMC, SRB and PAA.
[0022] In the present invention, the conductive agent includes at least one of conductive carbon black, natural graphite, artificial graphite, carbon nanotubes, graphene, and graphene nanosheets.
[0023] In the present invention, in the modified layer, the weight ratio of the modified material, the conductive agent, and the binder is 40-80:10-50:10-20; further, it can be 60-70:10-30:10-20. The present invention can efficiently adapt to the application requirements of negative electrode-free sodium batteries, especially high surface positive electrode-free sodium batteries, at low active material content, and can show excellent stability.
[0024] In the present invention, the thickness of the modified layer is less than or equal to 150 μm; preferably 20 to 100 μm; more preferably 35 to 65 μm, and further 48 to 54 μm. The present invention has shown that by controlling the composition and structure, and further coordinating the thickness control, the coordination of the material and structure can be further improved, which helps to further adapt it to the application requirements of the negative electrode-free battery and can make it show better electrochemical performance.
[0025] The present invention also provides a method for preparing the modified current collector for the negative electrode-free sodium metal battery, which comprises slurrying a binder, a conductive agent and a modified material with a solvent, coating the slurry on the surface of the planar current collector, and then drying the slurry.
[0026] The present invention also provides an application of the modified current collector for a negative electrode-free sodium metal battery, which is used as an electrode to prepare a negative electrode-free sodium metal battery.
[0027] The present invention can prepare the required negative electrode-free sodium metal battery by using the modified current collector described in the present invention based on the principle and characteristics of conventional negative electrode-free batteries.
[0028] The present invention also provides a negative electrode-free sodium metal battery, which comprises the modified current collector.
[0029] The negative electrode-free sodium metal battery of the present invention, in addition to comprising the modified current collector of the present invention, may have conventional components and structures.
[0030] For example, the negative electrode-free sodium metal battery of the present invention comprises a battery cell including a positive electrode, a barrier layer and the modified current collector which are compounded in sequence;
[0031] The barrier layer is a diaphragm, and the battery further comprises an electrolyte for soaking the battery core; or, the barrier layer is a solid electrolyte.
[0032] The negative electrode-free sodium metal battery of the present invention refers to a sodium metal battery in which the negative electrode active material is eliminated or exempted.
[0033] The negative electrode-free sodium metal battery of the present invention, in addition to using the modified current collector of the present invention, other components, parts and structures can be well known.
[0034] For example, the positive electrode of the present invention can be a conventional positive electrode in the industry, which includes a current collector and a positive electrode material loaded on the surface thereof, and the positive electrode material includes a conventional positive electrode active material, a binder and a conductive agent. In the positive electrode material, the components and proportions of the positive electrode active material, the binder and the conductive agent can all be conventional.
[0035] In the present invention, the negative electrode current collector is particularly suitable for high-surface-loaded positive electrodes that are difficult to adapt to the prior art. The high-surface-loaded positive electrode refers to a positive electrode in which the positive electrode active material loading is 15 mg·cm -2 Above (further 15~25mg·cm -2 )'s positive electrode.
[0036] Beneficial Effects
[0037] The modified current collector of the present invention can alleviate the volume expansion problem in the subsequent sodium deposition process; it can induce sodium to deposit uniformly on the current collector, and is conducive to forming a solid sodium-philic SEI layer, realizing highly reversible sodium deposition and stripping. The current collector can be applied to a negative electrode-free sodium metal battery to effectively reduce the sodium nucleation overpotential, which is conducive to effectively inducing sodium ion diffusion and uniform nucleation in the early stage of deposition, improving the reversibility of sodium deposition and stripping, thereby eliminating the growth of sodium dendrites and improving the cycle efficiency of the negative electrode-free sodium metal battery. More importantly, the negative electrode current collector of the present invention can meet the high-specification requirements of the high-surface-loaded positive electrode for the negative electrode current collector without a negative electrode, and can be assembled with it to obtain a high-performance negative electrode-free battery with a high-surface-loaded positive electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 is a full battery performance diagram of Example 1;
[0039] Figure 2 The full battery performance diagram of Examples 2E, 2F, and 2G;
[0040] Figure 3 This is the full battery performance diagram of Comparative Example 2. DETAILED DESCRIPTION
[0041] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention. Based on the implementation of the present invention, other embodiments obtained by those skilled in the art without creative labor are all within the scope of protection of the present invention.
[0042] In the present invention, the particle size of the modified material can meet the requirements for composite electrode preparation, for example, its particle size can be 10-1000 nm. As a typical embodiment, in the following case, the D50 of the modified material can be 150±20 nm.
[0043] Example 1
[0044] This embodiment prepares a negative electrode-free sodium metal battery current collector, and the specific preparation method includes the following steps:
[0045] S1. Place the modified material (in this case, yttrium oxide / yttrium titanate mixed particles, yttrium oxide: yttrium titanate is 15:85) with conductive carbon black and PVDF in a ratio of 7:2:1, with a total amount of 1g, in a mortar, grind them evenly and transfer them to a beaker, add 40 drops of NMP (N-methylpyrrolidone) drop by drop, and stir for 8 hours to obtain a modified mixed solution.
[0046] S2. Use a 50-micron scraper to evenly scrape it onto a clean aluminum foil current collector (coating thickness is 50±1μm), place it in a vacuum drying oven to dry, the drying temperature can be controlled at 80±10°C, and the drying time can be 8~9h to obtain the sodium-philic metal oxide composite coating current collector.
[0047] Performance Testing
[0048] In order to verify the performance of the current collector of the negative electrode-free sodium metal battery, the inventors used the negative electrode current collector of the negative electrode-free sodium metal battery to assemble a negative electrode-free sodium metal battery in the same way, and then tested the performance of the negative electrode-free sodium metal battery to examine the performance of the current collector of the negative electrode-free sodium metal battery. Specifically, it includes:
[0049] The prepared negative electrode-free sodium metal battery current collector was cut into samples with a diameter of 14 mm using a cutting machine as the negative electrode current collector (when assembling the battery, the modified layer of the negative electrode current collector faces the positive electrode direction), sodium iron pyrophosphate (NFPP) was used as the counter electrode (the positive electrode material includes NFPP, PVDF and conductive carbon black with a weight ratio of 9:0.5:0.5) to assemble the full battery, 1MNaFP6 / diethylene glycol dimethyl ether (DEGDME) as the electrolyte, and a porous single-layer polypropylene membrane as the separator. 2032 button cells were assembled in a glove box (high-purity argon atmosphere, in which the oxygen and water content is less than 0.1ppm). Then, the NFPP loading was 16mg·cm -2 Under load, use 100mA·g -1 The full battery was tested at a current density of 2.54 W and 30 °C.
[0050] Example 2
[0051] Compared with Example 1, the only difference is that the modified material of S1 is changed. The experimental groups are:
[0052] Group A: The modified material is yttrium oxide;
[0053] Group B: the modified material is yttrium carbonate;
[0054] Group C: modified material is yttrium titanate;
[0055] Group D: modified material is gadolinium oxide;
[0056] Group E (preferred group): the modified material is yttrium oxide and yttrium titanate in a weight ratio of 1:3;
[0057] Group F (preferred group): the modified material is yttrium titanate and yttrium carbonate in a weight ratio of 1:3;
[0058] Group G (preferred group): the modified material is gadolinium oxide and yttrium carbonate in a weight ratio of 1:3;
[0059] Comparison Group A: The modified material is zirconium oxide;
[0060] Comparative Group B: The modified material is strontium oxide;
[0061] Comparison Group C: The modified material is hafnium oxide;
[0062] Comparative group D: the modified material is lanthanum oxide;
[0063] Comparative Group E: The modified material is lead titanate;
[0064] The amount of modified material used and other operations and parameters are the same as those in Example 1, and the performance test is carried out according to the method of Example 1. The results are shown in Table 1.
[0065]
[0066] It can be seen from Examples 1 and 2 that the modified material of the present invention can adapt to the application requirements of negative electrode-free sodium ion batteries, especially the application requirements of high-surface-loaded positive electrode-free sodium batteries, and can improve its long-cycle stability. In particular, compared with Examples 1, 2E, 2G (oxidation-salt combination) and 2F (salt-salt combination), the combination of the special oxidation-type component A and the salt-type component B can unexpectedly enhance the synergy, unexpectedly further enhance the adaptability of the negative electrode-free current collector to the high-surface-loaded positive electrode, and unexpectedly show better cycle stability.
[0067] Example 3
[0068] Compared with Example 2A, the only difference is that the ratio of the composite coating material in step S1 is changed. The experimental groups are:
[0069] Group A: The ratio of nano-yttrium oxide particles, conductive carbon black and PVDF is 6:3:1;
[0070] Group B: The ratio of nano-yttrium oxide particles, conductive carbon black and PVDF is 5:3:2;
[0071] Group C: The ratio of nano-yttrium oxide particles, conductive carbon black and PVDF is 4:4:2;
[0072] Group D: The ratio of nano-yttrium oxide particles, conductive carbon black and PVDF is 2:6:2;
[0073] The performance test was carried out according to the method of Example 1. The results are shown in Table 2.
[0074]
[0075] It can be seen from Examples 2 and 3 that, using the process of the present application, the weight ratio of the modified case material, the conductive agent and the binder can be 20~80:10~60:10~20, preferably 40~80:10~50:10~20; further preferably 60~70:10~30:10~20.
[0076] Comparative Example 1
[0077] Compared with Example 1, the difference is that in S1, no conductive agent is added, and the modified material (yttrium oxide / yttrium titanate mixed particles, yttrium oxide: yttrium titanate is 15:85) is directly mixed with PVDF in a ratio of 8:2 to make a current collector, and the performance test is carried out according to the method of Example 1. The results are shown in Table 3.
[0078] Comparative Example 2
[0079] Compared with Example 1, the only difference is that steps S1-S2 are not performed, commercial carbon-coated aluminum foil is directly used as the negative electrode current collector without a negative electrode, and the performance test is carried out according to the method of Example 1. The results are shown in Table 3.
[0080] Comparative Example 3
[0081] Compared with Example 1, the difference is that no modifying material is added to S1, and the conductive carbon black and PVDF are directly made into a current collector in a ratio of 8:2, and the performance test is carried out according to the method of Example 1. The results are shown in Table 3.
[0082]
[0083] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A modified current collector for a negative electrode-free sodium metal battery, characterized in that: It includes a planar current collector and a single-layer modified layer compounded on its surface; and the modified layer is composed of a binder, a conductive agent and a modified material; The modified material comprises component A and component B; Wherein, the component A includes at least one of Y2O3 and Gd2O3; The component B includes at least one of yttrium carbonate, lead carbonate, tungsten carbonate, iridium carbonate, hafnium carbonate, molybdenum carbonate, yttrium titanate, iridium titanate, hafnium titanate, molybdenum titanate, gadolinium carbonate, and gadolinium titanate; In the modified material, the weight ratio of component A to component B is 10-30:70-90; Wherein, in the modified layer, the weight ratio of the modified material, the conductive agent, and the binder is 20~80:10~60:10~20; The thickness of the modified layer is 20~100μm; The modified current collector for a negative electrode-free sodium battery is a negative electrode current collector for a negative electrode-free sodium metal battery.
2. The modified current collector for a negative electrode-free sodium metal battery according to claim 1, characterized in that: The planar current collector is a conductive metal foil; The binder includes at least one of PVDF, CMC, SRB and PAA; The conductive agent includes at least one of conductive carbon black, natural graphite, artificial graphite, carbon nanotubes and graphene.
3. The modified current collector for a negative electrode-free sodium metal battery according to any one of claims 1 to 2, characterized in that: The weight ratio of the modified material, the conductive agent and the binder is 60-70:10-30:10-20.
4. The modified current collector for a negative electrode-free sodium metal battery according to claim 1, characterized in that: The thickness of the modified layer is 35~65μm.
5. The modified current collector for a negative electrode-free sodium metal battery according to claim 4, characterized in that: The thickness of the modified layer is 48~54μm.
6. A method for preparing a modified current collector for a negative electrode-free sodium metal battery according to any one of claims 1 to 5, characterized in that: The binder, the conductive agent and the modified material are slurried with a solvent, and then coated on the surface of the planar current collector, and then dried to obtain the product.
7. An application of the modified current collector for a negative electrode-free sodium metal battery according to any one of claims 1 to 5, characterized in that: It is used as an electrode to prepare a negative electrode-free sodium metal battery.
8. A negative electrode-free sodium metal battery, characterized in that: A modified current collector comprising any one of claims 1 to 5.
Citation Information
Cited By
Aluminum foil for negative-electrode-free sodium battery and preparation method of aluminum foil
CN120536779A
Preparation method and application of monodisperse metal site modified negative-electrode-free sodium metal battery current collector
CN122599344A
